METHODOLOGY OF USING THE HERITAGE OF CENTRAL ASIAN THINKERS IN THE FORMATION OF ECOLOGICAL THINKING IN PRIMARY EDUCATION (World Bulletin of Social Sciences, 2021)
This article aims to improve the use of the heritage of Central Asian thinkers in the formation of ecological thinking in primary school students, to identify opportunities for the development of ecological thinking in primary school students, to create a mechanism of links between ecological phenomena and processes in primary school students. , the conscious mastery of learning materials through the application of skills, competencies and competencies in new situations, the use of the heritage of Central Asian thinkers in the study of problems related to the relationship between man and nature, the integration and integration of knowledge in various disciplines using modern educational technologies
Keywords: Primary school; ecological thinking; ecological phenomena and processes; skills